Health Belief Model Keteraturan Pemeriksaan Antenatal Ibu Hamil Selama Pandemi Covid-19 - Nisa, Juhrotun; Rahmanindar, Nora (Universitas Tribhuwana Tunggadewi, 2023)
During the Covid-19 pandemic, maternal and neonatal death still becomes a challenging issue in Indonesia, especially since there was a social restriction on maternal and newborn health services. Pregnant women are advised to perform a pregnancy check-up during the pandemic, but most are reluctant due to afraid of being infected with the virus. The health belief model is used to analyze the assessment of individual health actions. The study aimed to determine the relation of the health belief model in antenatal examinations during the covid-19 pandemic. This research was a quantitative study with a cross-sectional approach. The population was whole pregnant women in the Dukuhwaru Health Center as many as 208 people. About 53 people sample recruited using accidental sampling techniques. Independent variables include perceptions of vulnerability, perceptions of seriousness, perception of threats, perception of benefits, perception of obstacles, and cues to action, while the dependent variables are the regularity of pregnant women in conducting antenatal care examinations. Data was collected through questionnaires and analyzed using Fisher's Exact test. The results showed that there was a relationship between the perception of seriousness (p=0.03), perception of threat (p=0.000), and perception of obstacles (p=0.04) with the regularity of antenatal checks. However, there was no significant correlation between perception of susceptibility (p=0.46), perception of benefit (p=0.07), and cues for action (p=1) to the regularity of antenatal checks. 3 out of 6 of the health belief model factors were related to the regularity of antenatal checks. The regularity of antenatal visits on the incidence of Covid-19 needs to be explored in subsequent studies.